Urban heat island analysis using the 'local climate zone' scheme in Presidente Prudente, Brazil - Cardoso, Renata dos Santos [UNESP]; Amorim, Margarete Cristiane de Costa Trindade [UNESP] (Univ Alicante, 2018)
Although urban heat islands (UHIs) have been widely studied, a recent climate-based classification of urban and rural landscapes provides a new framework for UHI researchers. Based on the Local Climate Zone (LCZ) system, we studied heat islands in a tropical city, analysing the effects of urban morphology and surface cover on UHI intensity. Mobile measurements were taken in Presidente Prudente, Sao Paulo, Brazil, on five winter evenings (June and July 2014). Observed temperatures across the city show compact built zones with higher temperatures, followed by open midsize, lightweight low-rise, and low plants zones. A maximum nocturnal temperature difference of more than 5 degrees C was detected between areas with significant differences in physical characteristics (Delta T (LCZ 24-D)), whereas average inter-zone thermal differences reached 3.8 degrees C (Delta T (LCZ 3-D)).
Keywords: Urban climate; urban heat island intensity; mobile traverses; tropical city